The Compatibility Analysis of Human Resources Competencies of Makassar New Port (MNP) and its Curriculum - Syamsiah, Sitti; Fauzi, Ahmad; Djabier, Abdoellah; Nurwahidah, Nurwahidah (Jurnal Pendidikan dan Pengajaran, 2021)
Human resources or HR are needed by companies at various scales, be it a large scale or even a small scale. Makassar New Port as a modern organization that developed kept up with the times, implemented a high competency standard in every level of work unit. To analyze the compatibility analysis of human resources competencies of Makassar New Port (MNP) towards curriculum of diploma IV port and shipping management department. The research was held in Politeknik Ilmu Pelayaran Makassar. The aim of this research to map the competencies of Makassar New Port Human Resources related to Diploma IV Port and Shipping Management Department Curriculums. The main informants in this research were the MNP staff who were assigned as many as 7 informants. The subjects in this study were 44 Makassar New Port employees, but only 7 were the research subjects. The location of this research was carried out at the Makassar New Port Office. The research was conducted in the Even semester in Academic Year 2019/2020, which was from February to October 2020. Data were collected by using in-depth interviews and observation methods the result of the research mentioned that there are 3 variables should be developed to be qualified as Makassar New Port Human Resources Competence which are; Port Business, Port and Logistics, and Port Management. The research results were a consensus obtained from all respondents regarding the variables that affect port competence. And there are 3 variables that have the potential to be developed, namely port business, ports and logistics, and port management.Â